Prognostic factors in mesial temporal lobe epilepsy surgery - DANIEL M. S. PREVEDELLO; MARCOS C. SANDMANN; ALOIS EBNER (Arquivos de Neuro-Psiquiatria)
Eighty-four patients submitted to anterior temporal lobectomy were evaluated retrospectively in order to correlate the different type of simple partial seizure (SPS) and their prognostic implications in patients with mesial temporal sclerosis. The patients were divided in two groups following the classification of Engel; Group 1 (53 patients) included patients Class I (without seizures or of good outcome) and Group 2 (31 patients) included Classes II, III and IV (with seizures or of bad outcome). The two groups were compared and results showed no statistical difference in relation to the demographic aspects as sex, side of surgery, age at onset of seizures and time of the patients' postoperative follow-up. Statistical analysis revealed no relationship between type of SPS and outcome. SPS did not show a statistical value in localizing the side of pathology. However, when the two groups were compared statistically in terms of patients' ages at the time of surgery, and the time elapsed from the onset of the seizures to the surgical intervention, it was observed that Group 1 (of good outcome) had seizures for smaller interval (p <0.05) and was operated at an earlier age (p<0.02) than Group 2 (of bad outcome). The presence or the type of SPS can not be used as a prognostic measure; surgical therapy must be considered as soon as clinical resistance is demonstrated.